(untitled) (Eurasian Research Bulletin, 2024)
The Progress in International Reading Literacy Study (PIRLS) International Assessment Program is a vital tool for evaluating and enhancing educational integration across global contexts. This paper explores the effectiveness of using PIRLS in educational integration, examining its impact on policy formulation, curriculum development, teacher training, and student outcomes. PIRLS data provides valuable insights into education systems’ strengths and weaknesses, informing evidence-based policies and promoting educational equity. Moreover, PIRLS influences curriculum development by identifying areas for improvement and informing teaching strategies.